Studi Literatur: Aktivitas Antidiabetes Bawang Dayak (Eleutherine americana) dan Serai (Cymbopogon citratus) - Miranda Aurora Pratiwi; Febrina Mahmudah; Yurika Sastyarina (Proceeding of Mulawarman Pharmaceuticals Conferences, 2020)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia. The Indonesian government is currently advising the public to consume traditional-based medicines because of their low side effects. One of the traditional medicines used is lemongrass and dayak onions. This study aims to determine the chemical compound content and antidiabetic activity of lemongrass and dayak onions. The research method used is the literature review method. Data searches were performed online on the PubMed, Science Direct, Google, Elsevier, and Google Scholar databases as well as other journal search websites. The scientific journals used are scientific journals published in the last 13 years. From 9 literature that has been studied, it shows that dayak onion tubers identify the presence of tannin compounds, saponins, flavonoids, alkaloids, steroids, terpenoids, glycosides, and anthraquinones while lemongrass contains tannin compounds, saponins, flavonoids, alkaloids, steroids, terpenoids, essential oils, phenolic, anthraquinones, carbohydrates, and glycosides. From 14 literature it is known that dayak onion tubers and lemongrass have antidiabetic activity. Compounds that have anti-diabetic activity properties include flavonoids, tannin and alkaloids contained in dayak onion and lemongrass, other than that essential oils contained in lemongrass.